GAS PHASE STRUCTURE AND STABILITY OF COMPLEX FORMED BY H2O, NH3, H2S AND THEIR METHYL DERIVATIVES WITH THE CATION CO2+ - Cahyorini Kusumawardani (Indonesian Journal of Chemistry, 2004)
Ab initio molecular orbital calculations at the Hartree-Fock-Self Consistent Field (HF-SCF) have been performed in order to determine the structure and gas phase energies of complex formed by the Lewis bases of H2O, NH3, H2S and their methyl derivatives with the cation Co2+. The relative basicities of the base studied depend on both the substituent. The gas-phase interaction energies computed by the SCF method including electron correlation Møller-Plesset 2 (MP2) dan Configuration Iteration (CI) were comparable in accuracy. The binding energies computed by these two methods reach the targeted chemical accuracy.